Drying Kinetics in Building Materials and Components The Interface Influence - Delgado, João M. P. Q.; Azevedo, António C.; Guimarães, Ana S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This work presents an extensive experimental characterisation of two different ceramic brick blocks with different interface, at different heights, during the drying process. First, a laboratory characterization of the building material used (ceramic bricks and different mortars) is presented, showing their hygrothermal, mechanical and thermal properties, namely, bulk porosity and density, water vapour permeability, capillary absorption, retention curve, moisture diffusivity as a function of moisture content and thermal conductivity. Moreover, the moisture transfer in multi-layered systems was analysed in detail taking into account the interface contact between the building elements.
Introduction -- Hygrothermal Properties of the Tested Materials -- Interface Influence during the Drying Process -- Conclusions.
Keywords: Building materials; Materials -- Analysis; Structural Materials; Building Materials; Characterization and Analytical Technique